Individual-level and area-level socioeconomic status (SES) and schizophrenia: cross-sectional analyses using the evidence from 1.9 million Chinese adults. Issue 9 (4th September 2019) - Luo, Yanan; Zhang, Lei; He, Ping; Pang, Lihua; Guo, Chao; Zheng, Xiaoying
Abstract : Objectives: Health disparities in schizophrenia are well established. However, it is less understood whether area-level socioeconomic status (SES) is differentially associated with schizophrenia depending on individual-level SES. Therefore, using a nationally large representative data, this study investigated the association between individual-level SES, area-level SES and their interaction with schizophrenia in Chinese adults from a multilevel perspective. Setting: Household interviews in 734 counties (districts), 2980 towns (streets) and 5964 communities (villages) from 31 provinces, People's Republic of China, as part of the cross-sectional survey of Second China National Sample Survey on Disability. Participants: 1 909 205 men and women aged 18 years old and above. Primary and secondary outcome measures: A screen followed by clinical diagnosis was used to identify schizophrenia, and schizophrenia was ascertained according to the International Statistical Classification of Diseases, 10th Revision (code F20). Results: 1-SD increase in individual SES was associated with decreased risk of schizophrenia ( OR =0.45, 95% CI 0.43 to 0.46). 1-SD increase in area-level SES was associated with increased risk of schizophrenia ( OR =1.30, 95% CI 1.24 to 1.37). The interaction of individual SES and area-level SES was statistically significant ( OR =1.05, 95% CI 1.02 to 1.08); as the level of area SES increased, schizophrenia risk of lower SES people grew faster than the risk of higher SES people. Conclusions: Area-level SES is particularly important to mental health of low SES individuals, with low SES people in high SES counties having the highest risk of schizophrenia than other groups. Action to reduce SES disparities in schizophrenia will require attention to the area-level context of low SES adults.